Efficiency of Microfinance Institutions in Latin America and Asia - Zetek, Pavel; Witzany, Jiří, 1966-; Srnec, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The first chapter provides a comprehensive overview of microfinance academic literature with emphasis on recent innovations, trends and efficiency. In particular, we focus on controversial issues of microfinance, such as commercialization, regulation, interest rate policy and the balance between outreach and performance of MFIs. The next chapter especially investigates the role of public expenditures and general government debt in microfinance performance in Latin America and the Caribbean. Microfinance institutions finance their business activities primary with clients' deposits, equity or with external funding. The aim of the third chapter is to verify whether the external funding, macroeconomic development and the size of banking sector have some impact on a microfinance performance. This study investigates, as well, the possible reasons why many microfinance institutions have gradually experienced a decrease in the share of female borrowers in their portfolios over the last few years. The final chapter is focused on the impact of macroeconomic environment and internal variables of the microfinance sector on microfinance interest rates.
Vedoucí práce: Jiří Witzany
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations